S’affranchir des distances : le web de la « diaspora » réunionnaise - Michel Watin; Eliane Wolff (Netcom)
The idea of migration amongst the Reunionese was up until the 1970s associated with exile. Such perceptions have however undergone changes since the end of the XXe century with the ubiquity and accessibility of new information and communications technologies. "Connected" migrants have created an e-diaspora, indissociably "on line" and "off line", asserting themselves within Reunionese society. Having been for a longtime withdrawn from the world, Reunion Island must now include her "ultramarines" citizens and rethink her spatial boundaries which today stretch across the world.